Shelley: Also Known as Shirley - Shelley Winters (New York Ballantine Books, 1981)
The electrifying and outspoken memoirs of an earthy and unusually intelligent actress. In a book as gutsy as the lady herself, Shelley Winters tells of the street-smart kid from Brooklyn who crashed Hollywood as a harem-girl sexpot. The Blonde Bombshell fought to make it as a serious actress and walked off with two Oscars. With exciting romances along the way--Lawrence Tierney, John Ireland, Errol Flynn, Burt Lancaster, Marlon Brando, William Holden--ending with her explosive and violent marriage to Italian actor Vittorio Gassman, she tells of her struggle for a successful career and a happy home life. Her book crackles with rich humor; it reads like a novel, with continuing characters like her roommate Marilyn Monroe, her Actors Studio buddy James Dean, her friend and sometimes romantic interest Farley Granger, mentors Max Reinhardt, Lee Strasberg, and Charles Laughton, and her loyal sister Blanche. With an overall warm Jewish family feeling, she describes bosses like Harry Cohn and Howard Hughes (she liked them both, though Harry fired her as a failed sex object), respected coworkers like Ronald Colman, Montgomery Clift, and Robert Mitchum, and directors like George Cukor, George Stevens, and Paul Mazursky. This is a courageous and honest book in which one of America's favorite personalities levels with the reader about the content and meaning of her life.
Keywords: Literature (3GdCOHs; General -- United States -- Biography; Motion picture actors and actresses